The Study of Semen Quality for Evaluation of Male Factor Infertility - Khanam, Mafruha; Banerjee, Aditi; Jerin, Jesmin; Fazyl, Mohamed Mazih (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: The global infertility rates are increasing at an alarming pace.Standard semen analysis is the basic and initial investigation in clinical practice for understanding male infertility. The objective of this study is to evaluate male infertility by studying the quality of semen according to the WHO protocols, identify the semen abnormalities to correlate the relationship between semen parameters and infertile couples. Materials and methods: This is a cross-sectional prospective study conducted in Surgiscope Fertility Centre, Chattogram, Bangladesh over 9 months on 1348 couples who received services from the fertility centre from November 2018 to July 2019. Multiple variables were selected such as, patient parameters like age of the couple, smoking history, duration of infertility, semen abnormalities which were recorded and statistically analyzed. The procedure and reference values were according to the WHO guidelines 2010. Results: The minimum age of the patients was 19 and the maximum age of the patients was 60 with a mean age of 33.3 +/- 0.5 years.The majority of the patients whose wives conceived were between the ages of 34 to 44 years and the lowest number of patients whose wives conceived were 55+ years. Moreover,359 patients (26.63%) conceived while 989 patients (73.37%) did not conceive.No significant relationship between number of conceptions and addiction was recorded. There is a statistically significant negative relationship between total motile sperm and age of patient and a marginally positive relationship between the number of sperm and total motility. Conclusion: This study showed a higher incidence of abnormal semen quality among husbands of infertile couples in our population. This revealed the importance of emphasizing on the need for managing male infertility. JCMCTA 2020 ; 31 (1) : 13-18